Extraction and HPLC Analysis of Tanshinone I, Tanshinone IIA and Cryptotanshinone from Salvia miltiorrhiza Bunge - Wan, X.; Tian, M.; Row, K.H. (Asian Journal of Chemistry, 2010)
In the present work, simultaneous extraction and separation of tanshinone I, tanshinone IIA and cryptotanshinone has been developed and validated from Salvia miltiorrhiza bunge. The extracts of the tanshinones were separated on a C18 column with the mobile phase composed of methanol-water (78:22, v/v, containing 0.5 % v acetic acid) at a flow-rate of 0.5 mL/min. The calibration was linear in a range of 0.1-500.0 μg/mL for these three compounds. The extracted amounts are 0.0091 mg/g for the tanshinone I, 0.12 mg/g for the tanshinone IIA and 0.15 mg/g for the cryptotanshinone.